2004
DOI: 10.1097/01.bpb.0000124491.13918.b7
|View full text |Cite
|
Sign up to set email alerts
|

Clubfoot release in myelodysplasia

Abstract: The purpose of this study was to evaluate our experience with treatment of clubfoot in myelomeningocele. We evaluated 45 children with clubfoot surgically treated at a mean age of 36 months. We evaluated each patient's medical record and performed a physical examination. Based on the clinical criteria by de Carvalho Neto, we obtained 61% good results, 26% fair results and 13% poor results. Neither age at surgery nor neurosegmental level have any statistical influence on final outcome. We find that a radical po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 8 publications
1
33
0
Order By: Relevance
“…However, the use of the Ponseti method to address clubfoot deformity in patients with myelomeningocele has not been reported, to our knowledge. Currently, the recommended treatment for these patients, who generally present with stiffer, more recalcitrant clubfeet, has been extensive soft-tissue releases performed either primarily or following a period of serial casting [24][25][26][27][33][34][35] . This type of surgery has been shown to be associated with a Anteroposterior radiograph of the tibia and fibula of a patient in the myelomeningocele group (Case 6; see Appendix), demonstrating distal tibial and fibular shaft fractures that occurred after the child was placed into the foot abduction brace at twenty weeks of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of the Ponseti method to address clubfoot deformity in patients with myelomeningocele has not been reported, to our knowledge. Currently, the recommended treatment for these patients, who generally present with stiffer, more recalcitrant clubfeet, has been extensive soft-tissue releases performed either primarily or following a period of serial casting [24][25][26][27][33][34][35] . This type of surgery has been shown to be associated with a Anteroposterior radiograph of the tibia and fibula of a patient in the myelomeningocele group (Case 6; see Appendix), demonstrating distal tibial and fibular shaft fractures that occurred after the child was placed into the foot abduction brace at twenty weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the reported successful treatment of idiopathic clubfeet with use of the Ponseti method 19,20,23 , we are not aware of any reports on the use of the Ponseti method for patients with myelomeningocele. On the contrary, clubfeet associated with myelomeningocele traditionally have been treated with extensive soft-tissue release surgery, with many short-term complications having been reported, including skin complications related to the lack of normal sensation in the lower limbs 24 , recurrent deformities 25,26 , and the need for revision and salvage procedures 24,[26][27][28] . We are not aware of any long-term follow-up studies investigating the outcomes for these patients.…”
mentioning
confidence: 99%
“…Many factors may contribute to the development of clubfoot in patients with spina bifida, including spasticity, intrauterine positioning, contractures, and muscle imbalance. For instance, in a patient with low-lumbar level of involvement, clubfoot may develop due to either retained activity or contracture of the tibialis muscles in combination with the functional absence of the peroneal muscles [12]. Additionally, the incidence of clubfoot varies with the neurologic level of involvement of the patient.…”
Section: Clubfootmentioning
confidence: 99%
“…Although the outcome seems to vary with the motor level of involvement, overall, good results have been reported in 61-83% of patients after surgical release [10][11][12]. de Carvalho et al reported 50% poor results in patients with thoracic and high-lumbar level of involvement compared to only 11% poor results in patients with low-lumbar and sacral levels of involvement [11].…”
Section: Clubfootmentioning
confidence: 99%
See 1 more Smart Citation